EFISIENSI PRODUKSI USAHATANI CABAI MERAH (Capsicum annuum L.) (STUDI KASUS: DI DESA SUMBEREJO, KECAMATAN BATU) - Ludovikus Ronaldus Unta; Agnes Quartina Pudjiastuti; A. Yusuf Kholil (Universitas Tribhuwana Tunggadewi, 2020)
The development of horticultural commodities is quite beneficial because it is supported by the potential of natural resources, human resources, availability of technology, and market absorption, one of which is red chili. This study aims to analyze the factors that influence the production of red chili farming in the Sumberejo village and the efficiency of the use of production factors (land area, seeds, manure, TSP, NPK, urea, labor, and pesticides). The data analysis method used is the Cobb-Douglas production function using multiple regression analysis, validity and reliability tests, classical assumption tests, model suitability (goodness of fit model), and efficiency analysis. The results showed that the simultaneous use of production factors of land area, seeds, manure, TSP, NPK, urea, labor, and pesticides had a significant effect on the production of red chili. Partially, the land area and seed production factors have a significant effect on the production of red chilies, while manure, TSP, NPK, urea, labor, and pesticides have no significant effect on the production of red chili. The results of the efficiency analysis show that the production factors of land area, seeds, manure, urea fertilizer, and labor are technically efficient because they are located in a rational area and technically, TSP, NPK, and pesticides are not efficient. In terms of price efficiency, the use of production factors is not efficient for land area, seeds, TSP fertilizers, NPK fertilizers, and pesticides have not reached economic efficiency. Other production factors such as manure, urea fertilizer, and labor are not economically efficient, so the use of inputs must be added to obtain maximum production.